The Relationship Between the Quality of Library Image at DPKD of South Tangerang City Library - Bakhtiar, Dharuri; Bakhtiar, Dharendi (Department Library of Governance Institut of Home Affairs, 2023)
Abstract Background/Problem Statement: This study aims to determine the relationship between the quality of library services and the image of the South Tangerang City DPKD Library in an effort to improve the services available in the library. Objectives: This study aims to determine the relationship of librarian performance in service, the relationship of information quality and information access, the relationship of library facilities and the quality of library services with the image of the library at the South Tangerang City DPKD Library. Method: This study used a quantitative approach with Pearson product moment correlation analysis. Result: The first hypothesis test conducted in this study shows that the affect of service dimension is significantly related to the library image, the resulting correlation coefficient of 0.542 is in the medium category. Furthermore, the results of the second hypothesis test show a significant relationship between the information control dimension and the library image, the correlation coefficient of 0.684 is in the medium category. The third hypothesis test results show a significant relationship between the library as place dimension and the library image, the correlation coefficient of 0.685 is in the medium high category. Conclusion: From some of the shortcomings of the description above, the author concludes that the quality of DPKD Library services is running quite effectively. Keywords: Library service quality; Library image; Public Library